"Harmonic and intermodulation performance of class-AB stages" - Abuelma’atti, M.T. (2007)
A new technique for predicting the harmonic and intermodulation performances of class-AB stages is presented. The proposed technique is based on modelling the transfer characteristic of the class-AB stage using a Fourier-series approximation. The number of terms of the Fourier-series is decided based on the required accuracy and the coefficients of the series are obtainable using simple hand calculations. The results obtained are in excellent agreement with simulation results and confirm that the intermodulation performance is dominant compared to the harmonic performance.